Pengenalan Sel Acute Lymphoblastic Leukemia (All) Dengan Menggunakan Metode Jaringan Syaraf Tiruan - Galih Dwi Saputra; Shofiya Syidada (Informatics Engineering Department-UWKS, 2017)
Leukemia is one cancer that attacks white blood cells. ALL is a dangerous type of acute leukemia. The identification of leukemia that still uses manual methods makes it difficult for researchers to identify. In this study, the researchers made a way of identifying acute lymphoblastic leukemia cell in white blood cell image by way of image processing. Processes in image processing include image segmentation, feature extraction, and image identification. The method used in image segmentation with k-means clustering and for image identification is used Artificial Neural Network method. The white blood cell image tested using this application will be evaluated in an accurate way.